DEVELOPMENT OF MODERN FILM TECHNOLOGIES IN UZBEKISTAN, THEIR ECONOMIC IMPACT, AND TRANSFORMATION PROCESSES IN THE MEDIA INDUSTRY - Baymuxamedova Dilnoza Bakhtiyorovna (Modern American Journals, 2025)
This article is devoted to the scientific analysis of the introduction of modern film technologies in Uzbekistan, their economic and creative impact on the media industry, and the mechanisms of transformation in film production processes. The research employs a combination of qualitative and quantitative methods and examines comprehensive practical data obtained from film studios, television channels, advertising agencies, and independent content producers. The rapid popularization of digital camera systems, drone cinematography, VFX and CGI technologies, color grading, and real-time production tools has been found to accelerate production workflows, optimize budgets, expand creative freedom, and increase content export potential. The results show that the technological modernization of Uzbekistan’s film industry is bringing about deep structural changes not only in equipment renewal but also in the economic model of the market, labor distribution, creative processes, and consumer demand. At the same time, challenges such as the shortage of qualified specialists, discrepancies between technical education and global standards, and the high dependence on imported equipment have also been identified. Overall, the integration of modern film technologies is emerging as one of the key factors enhancing the competitiveness of Uzbekistan’s media market and creating new professions and economic opportunities.
Keywords: Modern film technologies; digital cinematography; media industry; editing and post-production; VFX; CGI; drone cinematography